Practical aspects in the use of passive immunization as an alternative to attenuated viral vaccines. Issue 22 (11th May 2016) - Aizenshtein, Elina; Yosipovich, Roni; Kvint, Moran; Shadmon, Roy; Krispel, Simcha; Shuster, Efrat; Eliyahu, Dalia; Finger, Avner; Banet-Noach, Caroline; Shahar, Ehud; Pitcovski, Jacob
Abstract: Passive immunization as a method to protect birds has been tested for many years and shown to be effective. Its advantages over active vaccination include no use of partially virulent viruses, overcoming the gap in the level of protection at young age due to interference of maternal antibodies to raise self-immune response following active vaccination and the possible immunosuppressive effect of attenuated vaccine viruses. However, a major obstacle to its implementation is its relatively high cost which is dependent, among other things, mainly on two factors: the efficacy of antibody production, and the use of specific pathogen-free (SPF) birds for antibody production to avoid the possible transfer of pathogens from commercial layers. In this study we show efficient production of immunoglobulin Y (IgY) against four different pathogens simultaneously in the same egg, and treatment of the extracted IgY with formalin to negate the need for SPF birds. Formalin, a common registered sterilization compound in vaccine production, was shown not to interfere with the Fab specific antigen binding or Fc-complement activation of the antibody. Following injection of 1-day-old broilers with antibodies against infectious bursal disease virus, protective antibody levels were acquired for the entire period of sensitivity to this pathogen (35 days). Passive vaccination with formalin-sterilized IgY against multiple antigens extracted from one commercial egg may be a cost-effective and advantageous complementary or alternative to attenuated vaccines in poultry.